Does Uncertainty in Climate Policy Affect Economic growth? Empirical Evidence from the U.S. - Savaş Çelik, Burcu; Özarslan Doğan, Başak (Ekonomika, 2024)
This study aims to empirically investigate the short- and long-term effects of climate policy uncertainty on economic growth in the U.S. for the years 1990-2020. In the study, total workforce, foreign direct investments, and financial development variables were also selected as control variables, and the effects of these variables on economic growth were examined. The study used the ARDL bounds test approach to investigate the cointegration between the variables. The findings confirm the existence of a positive and statistically significant relationship between climate policy uncertainty and economic growth in the sample period in the U.S. In addition, the effects of total labor force, foreign direct investments, and financial development on economic growth were found to be positive and statistically significant in the study.